Major Depressive Disorder Cognitive and Neurobiological Mechanisms - Kim, Yong-Ku (IntechOpen, 2015)
Major depressive disorder (MDD) is a complex and heterogeneous disorder, phenotypically and biologically. MDD may be caused by complex interaction between genes and environment in susceptible individuals. Thus, a combination of certain genetic polymorphism, environmental stress, and personal susceptibility ultimately may induce MDD. Gene-environment interactions in the pathophysiology of MDD lead to advancement in personalized medicine by means of genotyping for inter-individual variability in drug action and metabolism. Gene-environment interactions may explain why some subjects become depressed while others remain unaffected. The aim of this book is to describe current knowledge of MDD from the point of view of neurobiology, molecular genetics and cognition. The authors address a deep understanding of cognitive and neurobiological mechanisms involved in MDD.